Pelindungan Hukum Terhadap Sumber Daya Genetik dan Pengetahuan Tradisional (SDG-PT) Pasca Diundangkannya Undang-Undang Nomor 13 Tahun 2016 Tentang Paten - Ferianto Ferianto; Tommy Hendrix; Tuthi’ Mazidatur Rohmah (JIPRO: Journal of Intellectual Property, 2020)
The huge potential of genetic resources has made Indonesia one of the goals of bioprospection and even biopiracy from other countries which has actually harmed the Indonesian state both legally and economically. Referring to the importance of managing genetic resources and traditional knowledge, there have been many political results of national law that have been created to regulate the protection and management of genetic resources and traditional knowledge. One of the products of the political law is Law no. 13 of 2016 concerning Patents. Therefore, this study aims to examine the legal protection aspects of genetic resources and traditional knowledge in terms of Law Number 13 of 2016 concerning Patents, opportunities and challenges for Indonesia in utilizing the protection of the SDG to empower an economy based on biodiversity and traditional knowledge. This research is a normative research with qualitative data analysis. Normative research is carried out with a literature study approach consisting of primary and secondary legal materials. The research results show that Law No. 13 Year 2016 regarding Patents have loaded a better legal protection against patent-based genetic resources and traditional knowledge (GR-TK) both preventive and repressive. The opportunity for GR-TK potential is if database can be managed centrally, systematically and completely, it will facilitate utilization and arrangement of benefit sharing access so that benefits felt by Indonesia as country that owns GR-TK are more optimal. The challenge faced is that management of GR-TK database systematically and completely by a special authority has not been established by Government. Arrangements regarding benefit sharing in GR-TK utilization has not made the technical regulations governing them.